Проблеми збереження архітектурного оздоблення - Радченко, А. (Інститут народознавства НАН України, 2007)
The article throws light upon some questions in conservation and renovation of villa decorations. Passport categories for registration and description of objects are proposed. It would be desirable to introduce a course of “Architectural Decor” for students of artistic wood-processing.